Role of sodium‐dependent Pi transporter/Npt2c on Pi homeostasis in klotho knockout mice different properties between juvenile and adult stages. Issue 3 (5th February 2020) - Hanazaki, Ai; Ikuta, Kayo; Sasaki, Shohei; Sasaki, Sumire; Koike, Megumi; Tanifuji, Kazuya; Arima, Yuki; Kaneko, Ichiro; Shiozaki, Yuji; Tatsumi, Sawako; Hasegawa, Tomoka; Amizuka, Norio; et al.
Abstract: SLC34A3/NPT2c/NaPi‐2c/Npt2c is a growth‐related NaPi cotransporter that mediates the uptake of renal sodium‐dependent phosphate (Pi). Mutation of human NPT2c causes hereditary hypophosphatemic rickets with hypercalciuria. Mice with Npt2c knockout, however, exhibit normal Pi metabolism. To investigate the role of Npt2c in Pi homeostasis, we generated α‐klotho −/− /Npt2c −/− (KL2cDKO) mice and analyzed Pi homeostasis. α‐Klotho −/− (KLKO) mice exhibit hyperphosphatemia and markedly increased kidney Npt2c protein levels. Genetic disruption of Npt2c extended the lifespan of KLKO mice similar to that of α‐Klotho −/− /Npt2a −/− mice. Adult KL2cDKO mice had hyperphosphatemia, but analysis of Pi metabolism revealed significantly decreased intestinal and renal Pi (re)absorption compared with KLKO mice. The 1, 25‐dihydroxy vitamin D3 concentration was not reduced in KL2cDKO mice compared with that in KLKO mice. The KL2cDKO mice had less severe soft tissue and vascular calcification compared with KLKO mice. Juvenile KL2cDKO mice had significantly reduced plasma Pi levels, but Pi metabolism was not changed. In Npt2cKO mice, plasma Pi levels began to decrease around the age of 15 days and significant hypophosphatemia developed within 21 days. The findings of the present study suggest that Npt2c contributes to regulating plasma Pi levels in the juvenile stage and affects Pi retention in the soft and vascular tissues in KLKO mice. Abstract : SLC34A3/NPT2c/NaPi‐2c/Npt2c is a growth‐related NaPi cotransporter that mediates the uptake of renal sodium‐dependent phosphate (Pi). Mutation of human NPT2c causes hereditary hypophosphatemic rickets with hypercalciuria. Npt2c contributes to regulating plasma Pi levels in the juvenile stage and affects Pi retention in the soft and vascular tissues in KLKO mice.